THE ROLE OF ANTIOXIDANT THERAPY IN IMPROVING OVARIAN FUNCTION IN INFERTILE WOMEN - Davletova , D.M.; Kodirova , N.K. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
In infertile women, folliculogenesis and ovulation processes are often influenced by various factors, including oxidative stress. Antioxidants are crucial components that can help improve these processes by neutralizing free radicals and reducing oxidative stress in cells. Antioxidant therapy may prove to be effective in addressing infertility and ovarian dysfunction-related issues. This scientific work explores the role of antioxidants in folliculogenesis and ovulation, analyzing their potential impact on improving reproductive health.